Neutrophil to lymphocyte ratio as predictor for incident hypertension: a 9-year cohort study in Taiwan - Jhuang, Yi-Han; Kao, Tung-Wei; Peng, Tao-Chun; Chen, Wei-Liang; Li, Yen-Wei; Chang, Pi-Kai; Wu, Li-Wei (Hypertension research, 2019)
The neutrophil-to-lymphocyte ratio (NLR) has received much attention in recent decades and has been a novel inflammatory marker. NLR has been applied in predicting the prognosis of malignancies, mortality, and chronic diseases. Additionally, hypertension, defined as systolic blood pressure ≥ 140 mm Hg or diastolic blood pressure ≥ 90 mm Hg, a previous diagnosis of hypertension, and taking any antihypertensive drug, has been one of the most common chronic diseases in Asia and is currently the most important risk factor for cardiovascular diseases worldwide. Thus, we aimed to investigate the correlation between NLR and prevalent hypertension in the Taiwanese population. From the data of routine health checkups at the General Health Promotion Center in the Tri-Service General Hospital (TSGH), a total of 6278 participants were included. The NLR value was divided into tertiles. The Cox regression model revealed that the highest NLR group tended to be hypertensive (HR = 1.28, 95% CI 1.03–1.59) after adjustment. Individuals were also divided into age-specific, BMI-specific, or sex-specific groups; compared with the lowest NLR group, elderly individuals in the highest tertile of NLR were relatively likely to be hypertensive after covariate adjustment (HR = 1.88, 95% CI 1.19–2.96). Furthermore, a male group aged more than 60 years was reported to have a significant association with hypertension (HR = 1.84, 95% CI 1.06–3.18). However, there was no significant difference in the BMI-based stratified groups, even after adjustment. Our research revealed a significant association between the NLR and incident hypertension, especially in elderly or male Taiwanese individuals.